Future strategies for California’s zero-emission vehicle adoption using dynamical systems modeling - Aadhithiyan Subramaniyan; Timothy Fraser; Huaizhu Oliver Gao (Transportation Research Part D: Transport and Environment, 2026)

Ertugliflozin decreases the insulin spike in non-insulin dysregulated standardbred horses following intra-articular triamcinolone administration - Cara Darch; Timothy H. Hyndman; David Byrne; David Ian Rendle; Barny Fraser (Domestic Animal Endocrinology, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Machine learning in spatiotemporal PM2.5 hotspots analysis for better targeted mitigation strategies - Danni Lu; Alireza Yazdiani; Timothy Fraser; Mohammad Tayarani; H. Oliver Gao (Transportation Research Part D: Transport and Environment, 2025)

Prickly politics: How Rosa rubiginosa (Sweet-Briar Rose) divides rural communities, private landowners, and commercial players in South Africa - Grant D. Martin; Kim Canavan; Timothy Westwood; Gerald Chikowore; Gavin Fraser; Quinn Clark; Stephanie Payne; Sandy-Lynn Steenhuisen (South African Journal of Botany, 2025)

Who’s at the table? Disaster committee composition and policy pathways after Hurricane Sandy - Timothy Fraser; Lucy Hewitt; Jessica Chen; Matthew Cherkerzian; Vincent Rago; Daniel P. Aldrich (Journal of Environmental Management, 2025)

Driving climate action with the VISUALIZER: A dashboard for transportation emissions data analysis & visualization - Timothy Fraser; H. Oliver Gao (Urban Climate, 2025)

Cycling cities: Measuring urban mobility mixing in bikeshare networks - Timothy Fraser; Katherine Van Woert; Sophia Olivieri; Jonathan Baron; Katelyn Buckley; Pamela Lalli (Journal of Transport Geography, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

The role of financial incentives in promoting electric light commercial vehicles in the United States - Yan Guo; Timothy Fraser; Semida Silveira (Energy Policy, 2025)

Organic Phosphorus in the Terrestrial Environment: an Update on Current Research and Future Directions - Emileigh R. Lucas; Nhiem D. Nguyen; Luisella Celi; Leo M. Condron; Tandra D. Fraser; Timothy S. George; María de La Luz Mora; Nelly S. Raymond (Journal of Soil Science and Plant Nutrition, 2025)
In 2016, a group of experts convened to set priorities for organic phosphorus (P) research, addressing global issues, methodological strengths and weaknesses, and the benefits of understanding the organic P cycle. Seven years later, scientists and students with an interest in organic P reconvened to discuss progress and new insights, and this review highlights recent major research updates. Interest in organic P research has increased since 2016, and new priorities have emerged, including the impact of climate change on organic P, the influence of geopolitical crises on P supplies, and the adoption of sustainable practices like regenerative agriculture. Climate change was a central theme in the 2023 discussions, with an increased emphasis on integrating P and especially organic P into climate change research, which has traditionally focused more on carbon (C) and nitrogen (N). The discussions highlighted disparities in accessing analytical equipment globally, and its consequent impact on research quality and scope. To address these issues, coordinated efforts involving the research community, government policies, and international cooperation are needed, much the same as we see with the climate and biodiversity crises. Promoting sustainable agricultural practices, investing in soil health, and enhancing education and extension services are crucial. Future research should focus on standardizing analytical methods, integrating nutrient balance into models, and exploring soil-microbiome-plant interactions. Regular and intedisciplinary workshops, social media engagement, and the establishment of research networks are recommended to maintain momentum in organic P research. Raising public and stakeholder awareness about the importance of organic P is essential for advancing knowledge in this area.

A tale of many cities: Mapping social infrastructure and social capital across the United States - Timothy Fraser; Osama Awadalla; Harshita Sarup; Daniel P. Aldrich (Computers, Environment and Urban Systems, 2024)

The great equalizer? Mixed effects of social infrastructure on diverse encounters in cities - Timothy Fraser; Takahiro Yabe; Daniel P. Aldrich; Esteban Moro (Computers, Environment and Urban Systems, 2024)

Making MOVES move: Fast emissions estimates for repeated transportation policy scenario analyses - Timothy Fraser; Yan Guo; H. Oliver Gao (Environmental Modelling & Software, 2024)

How far I’ll go: Social infrastructure accessibility and proximity in urban neighborhoods - Timothy Fraser; Olivia Feeley; Andres Ridge; Ava Cervini; Vincent Rago; Kelly Gilmore; Gianna Worthington; Ilana Berliavsky (Landscape and Urban Planning, 2024)

Macroalgae exhibit diverse responses to human disturbances on coral reefs - Sara E. Cannon; Simon D. Donner; Angela Liu; Pedro C. González Espinosa; Andrew H. Baird; Julia K. Baum; Andrew G. Bauman; Maria Beger; Cassandra E. Benkwitt; Matthew J. Birt; Yannick Chancerelle; Joshua E. Cinner; et al. (Global Change Biology, 2023)
Scientists and managers rely on indicator taxa such as coral and macroalgal cover to evaluate the effects of human disturbance on coral reefs, often assuming a universally positive relationship between local human disturbance and macroalgae. Despite evidence that macroalgae respond to local stressors in diverse ways, there have been few efforts to evaluate relationships between specific macroalgae taxa and local human‐driven disturbance. Using genus‐level monitoring data from 1205 sites in the Indian and Pacific Oceans, we assess whether macroalgae percent cover correlates with local human disturbance while accounting for factors that could obscure or confound relationships. Assessing macroalgae at genus level revealed that no genera were positively correlated with all human disturbance metrics. Instead, we found relationships between the division or genera of algae and specific human disturbances that were not detectable when pooling taxa into a single functional category, which is common to many analyses. The convention to use percent cover of macroalgae as an indication of local human disturbance therefore likely obscures signatures of local anthropogenic threats to reefs. Our limited understanding of relationships between human disturbance, macroalgae taxa, and their responses to human disturbances impedes the ability to diagnose and respond appropriately to these threats.

Fleeing the unsustainable city: soft policy and the dual effect of social capital in hurricane evacuation - Timothy Fraser (Sustainability Science, 2022)

Grassroots vs. greenhouse: the role of environmental organizations in reducing carbon emissions - Timothy Fraser; Pinar Temocin (Climatic Change, 2021)

Unstable intraguild predation causes establishment failure of a globally invasive species - Quenton M. Tuckett; Amy E. Deacon; Douglas Fraser; Timothy J. Lyons; Katelyn␣M. Lawson; Jeffrey E. Hill (Ecology, 2021)
Biotic resistance is often posited, but rarely known, to be the cause of invasion failure. Competition and predation are the most frequently identified processes that may prevent or limit the establishment of nonnative species. Interactions between nonnative and native species that involve intraguild predation (IGP) are very common in nature, although theory predicts most IGP systems should be unstable and lead to extinction. If this prediction is true, the frequency of invasion failures due to IGP may be underappreciated because of their fleeting nature and, thus, studies of unstable IGP systems are lacking, despite the opportunities they offer for understanding the factors affecting their unstable dynamics. We investigated a failed invasion involving an IGP relationship. In Florida, the guppy ( Poecilia reticulata ), a worldwide invader, fails to establish in the presence of eastern mosquitofish ( Gambusia holbrooki ). We tested whether and how resident mosquitofish cause guppy invasion failure using replicated mesocosm and aquarium trials. Both the predator and competitor components of the IGP relationship were strongly asymmetrical, with large impacts on guppies. We identified two effects, direct consumption of neonates and aggressive interference competition, that limited survival and recruitment. The highly unstable nature of this IGP relationship is the primary cause of the failure of the guppy to establish in Florida. Our study shows that the transient nature of an ephemeral IGP relationship can yield important insights into the underlying causes of invasion failure, including the role of strong biotic resistance.

Correlates of bird collisions with buildings across three North American countries - Jared A. Elmore; Stephen B. Hager; Bradley J. Cosentino; Timothy J. O'Connell; Corey S. Riding; Michelle L. Anderson; Marja H. Bakermans; Than J. Boves; David Brandes; Eric M. Butler; Michael W. Butler; Nicolette L. Cagle; et al. (Conservation Biology, 2021)
Collisions with buildings cause up to 1 billion bird fatalities annually in the United States and Canada. However, efforts to reduce collisions would benefit from studies conducted at large spatial scales across multiple study sites with standardized methods and consideration of species‐ and life‐history‐related variation and correlates of collisions. We addressed these research needs through coordinated collection of data on bird collisions with buildings at sites in the United States (35), Canada (3), and Mexico (2). We collected all carcasses and identified species. After removing records for unidentified carcasses, species lacking distribution‐wide population estimates, and species with distributions overlapping fewer than 10 sites, we retained 269 carcasses of 64 species for analysis. We estimated collision vulnerability for 40 bird species with ≥2 fatalities based on their North American population abundance, distribution overlap in study sites, and sampling effort. Of 10 species we identified as most vulnerable to collisions, some have been identified previously (e.g., Black‐throated Blue Warbler [ Setophaga caerulescens ]), whereas others emerged for the first time (e.g., White‐breasted Nuthatch [ Sitta carolinensis ]), possibly because we used a more standardized sampling approach than past studies. Building size and glass area were positively associated with number of collisions for 5 of 8 species with enough observations to analyze independently. Vegetation around buildings influenced collisions for only 1 of those 8 species (Swainson's Thrush [ Catharus ustulatus ]). Life history predicted collisions; numbers of collisions were greatest for migratory, insectivorous, and woodland‐inhabiting species. Our results provide new insight into the species most vulnerable to building collisions, making them potentially in greatest need of conservation attention to reduce collisions and into species‐ and life‐history‐related variation and correlates of building collisions, information that can help refine collision management.

Making conservation science more reliable with preregistration and registered reports - Timothy Parker; Hannah Fraser; Shinichi Nakagawa (Conservation Biology, 2019)

Japan’s mega solar boom: quantifying social equity expectations and realities at the local scale - Andrew Chapman; Timothy Fraser (Sustainability Science, 2019)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Vitamin D supplementation does not improve human skeletal muscle contractile properties in insufficient young males - Daniel J. Owens; Daniel Webber; Samuel G. Impey; Jonathan Tang; Timothy F. Donovan; William D. Fraser; James P. Morton; Graeme L. Close (European Journal of Applied Physiology, 2014)

Direct evidence that HSV DNA damaged by ultraviolet (UV) irradiation can be repaired in a cell type-dependent manner - Scott Millhouse; Xiaohe Wang; Nigel W. Fraser; Lisa Faber; Timothy M. Block (Journal of NeuroVirology, 2012)

Automated motion estimation of root responses to sucrose in two Arabidopsis thaliana genotypes using confocal microscopy - Nathalie Wuyts; A. Glyn Bengough; Timothy J. Roberts; Chengjin Du; M. Fraser Bransby; Stephen J. McKenna; Tracy A. Valentine (Planta, 2011)

Selective blockade of the orexin-2 receptor attenuates ethanol self-administration, place preference, and reinstatement - James R. Shoblock; Natalie Welty; Leah Aluisio; Ian Fraser; S. Timothy Motley; Kirsten Morton; James Palmer; Pascal Bonaventure; Nicholas I. Carruthers; Timothy W. Lovenberg; Jamin Boggs; Ruggero Galici (Psychopharmacology, 2011)

JNJ-39220675, a novel selective histamine H3 receptor antagonist, reduces the abuse-related effects of alcohol in rats - Ruggero Galici; Amir H. Rezvani; Leah Aluisio; Brian Lord; Edward D. Levin; Ian Fraser; Jamin Boggs; Natalie Welty; James R. Shoblock; S. Timothy Motley; Michael A. Letavic; Nicholas I. Carruthers; et al. (Psychopharmacology, 2011)

Evidence that herpes simplex virus DNA derived from quiescently infected cells in vitro , and latently infected cells in vivo , is physically damaged - Scott Millhouse; Ying-Hsiu Su; Xianchao Zhang; Xiaohe Wang; Benjamin P Song; Li Zhu; Emily Oppenheim; Nigel W Fraser; Timothy M Block (Journal of NeuroVirology, 2010)

Measuring anxiety- and locomotion-related behaviours in mice: a new way of using old tests - Leanne M. Fraser; Richard E. Brown; Ahmed Hussin; Mara Fontana; Ashley Whittaker; Timothy P. O’Leary; Lauren Lederle; Andrew Holmes; André Ramos (Psychopharmacology, 2010)

In vitro and in vivo characterization of JNJ-31020028 (N-(4-{4-[2-(diethylamino)-2-oxo-1-phenylethyl]piperazin-1-yl}-3-fluorophenyl)-2-pyridin-3-ylbenzamide), a selective brain penetrant small molecule antagonist of the neuropeptide Y Y2 receptor - James R. Shoblock; Natalie Welty; Diane Nepomuceno; Brian Lord; Leah Aluisio; Ian Fraser; S. Timothy Motley; Steve W. Sutton; Kirsten Morton; Ruggero Galici; John R. Atack; Lisa Dvorak; et al. (Psychopharmacology, 2010)

Herpes simplex virus type 1 ICP4 deletion mutant virus d120 infection failed to induce apoptosis in nerve growth factor–differentiated PC12 cells - Benjamas Aiamkitsumrit; Xianchao Zhang; Timothy M Block; Pamela Norton; Nigel W Fraser; Ying-Hsiu Su (Journal of NeuroVirology, 2007)

The stability of herpes simplex virus type I genomes in infected Vero cells undergoing viral induced apoptosis - Ying-Hsiu Su; Xianchao Zhang; Benjamas Aiamkitsumrit; Qiyi Tang; Gerd Maul; Nigel W Fraser; Timothy M Block (Journal of NeuroVirology, 2006)

Transcriptional profiling of the hyperthermophilic methanarchaeon Methanococcus jannaschii in response to lethal heat and non‐lethal cold shock - Boonchai B. Boonyaratanakornkit; Anjana J. Simpson; Timothy A. Whitehead; Claire M. Fraser; Najib M. A. El‐Sayed; Douglas S. Clark (Environmental Microbiology, 2005)
Summary Temperature shock of the hyperthermophilic methanarchaeon Methanococcus jannaschii from its optimal growth temperature of 85°C to 65°C and 95°C resulted in different transcriptional responses characteristic of both the direction of shock (heat or cold shock) and whether the shock was lethal. Specific outcomes of lethal heat shock to 95°C included upregulation of genes encoding chaperones, and downregulation of genes encoding subunits of the H + transporting ATP synthase. A gene encoding an α subunit of a putative prefoldin was also upregulated, which may comprise a novel element in the protein processing pathway in M. jannaschii . Very different responses were observed upon cold shock to 65°C. These included upregulation of a gene encoding an RNA helicase and other genes involved in transcription and translation, and upregulation of genes coding for proteases and transport proteins. Also upregulated was a gene that codes for an 18 kDa FKBP‐type PPIase, which may facilitate protein folding at low temperatures. Transcriptional profiling also revealed several hypothetical proteins that respond to temperature stress conditions.

The potential use of raman mapping to investigate in vitro deposition of combination pressurized metered-dose inhalers - D. Fraser Steele; Paul M. Young; Robert Price; Timothy Smith; Stephen Edge; David Lewis (The AAPS Journal, 2004)